2013
DOI: 10.1007/s10029-013-1098-3
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic repair for recurrent incisional hernias: a single institute experience of 10 years

Abstract: Surgical treatment for RIH remains controversial because of lack in literature of specific studies on this topic. Morbid obesity and large defects have been often associated with technical difficulties and worse results. Our 10 years' experience with LR provided satisfactory results in terms of PO morbidity and recurrence rate, despite any kind of patient selection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 29 publications
1
18
0
Order By: Relevance
“…Through technical improvement in the suturing concept and our growing experience, we managed to reduce the incidence of transient pain to a low acceptable rate of 3.24 % (VAS 5-7) that decreased to 2.56 % on a chronic pain stage, which is comparable to the literature. On the overall rate of late complications of 10.74 %, we noticed also that by reducing the dead space, the chronic pain, skin bulging, and rate of recurrence were reduced to, respectively, 2.56, 1.50, and 4.72 %. One case of mortality was due to a tracheal stenosis, responsible for an acute respiratory syndrome.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…Through technical improvement in the suturing concept and our growing experience, we managed to reduce the incidence of transient pain to a low acceptable rate of 3.24 % (VAS 5-7) that decreased to 2.56 % on a chronic pain stage, which is comparable to the literature. On the overall rate of late complications of 10.74 %, we noticed also that by reducing the dead space, the chronic pain, skin bulging, and rate of recurrence were reduced to, respectively, 2.56, 1.50, and 4.72 %. One case of mortality was due to a tracheal stenosis, responsible for an acute respiratory syndrome.…”
Section: Introductionmentioning
confidence: 85%
“…Indeed, the recurrence rate after LIVHR with wider mesh coverage ranges between 2.9 and 17.7 %, while it is mainly 12 % and reaches up to 32 % in exceptions in open repair with mesh [1,[4][5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Defect size remains a contentious issue in laparoscopic hernia repair, with some centres recommending open repair above a certain cut-off point, 6,14 and other centres imposing no limit. Some studies have reported no relationship between defect size and recurrence of hernia, 15,16 whereas others have reported an increased risk of recurrence with increasing defect size. 6,17 Patients may be dissatisfied with cosmetic outcome due to mesh eventration.…”
Section: Discussionmentioning
confidence: 99%
“…The surface under the cumulative ranking curve (SUCRA) simplifies the ranking of a treatment's probability of being better than another treatment, although it 35 150 (P) 40 13 Permanent and absorbable tacks with sutures Ferrari et al 36 69 (R) 41 73 Permanent tacks Ferrari et al 37 100 (I) 24 79⋅2 Permanent tacks Frantzides et al 38 208 (I) 24 173 Permanent staples Lahon et al 39 74 (I) 13 n.r. Permanent tacks Novitsky et al 40 163 ( 45 64 (66 P) 10 117⋅9 Permanent tacks with sutures Bucher et al 46 52 ( Values in parentheses are proportions unless indicated otherwise; *values are median (range) of mean and median values extracted from the individual studies.…”
Section: Network Meta-analysismentioning
confidence: 99%